2004
DOI: 10.1186/1471-2350-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Examination of NRCAM, LRRN3, KIAA0716, and LAMB1as autism candidate genes

Abstract: BackgroundA substantial body of research supports a genetic involvement in autism. Furthermore, results from various genomic screens implicate a region on chromosome 7q31 as harboring an autism susceptibility variant. We previously narrowed this 34 cM region to a 3 cM critical region (located between D7S496 and D7S2418) using the Collaborative Linkage Study of Autism (CLSA) chromosome 7 linked families. This interval encompasses about 4.5 Mb of genomic DNA and encodes over fifty known and predicted genes. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…Molecular Psychiatry study 185 similarly assessed several SNPs in the LAMB1 gene, and found association with the disorder for a haplotype consisting of two SNPs in intron 25. No exonic SNPs were associated with AD in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Psychiatry study 185 similarly assessed several SNPs in the LAMB1 gene, and found association with the disorder for a haplotype consisting of two SNPs in intron 25. No exonic SNPs were associated with AD in this study.…”
mentioning
confidence: 99%
“…The positive finding in the ASP, however, was again not replicated in the singleton IMGSAC sample, 184 and no association was found for variants in the NRCAM gene in the second study. 185 Taken together, LAMB1 remains an interesting candidate gene for AD, as LAMB1 encodes for the b1 chain of laminin, which is an important glycoprotein promoting neuronal migration and neurite outgrowth in the developing nervous system. 186,187 Variants in the protein-tyrosine phosphatase, receptor-type, zeta-1 (PTPRZ1) gene, which is highly expressed in the brain during embryogenesis, 188 have been assessed by two studies.…”
mentioning
confidence: 99%
“…Based on elaborate research regarding possible imprinted genes, fragile sites and duplications, candidate genes for several developmental disorders have been suggested, including candidate genes for autism. 71 Interestingly, for this chromosome there is a considerable overlap of the cytogenetic regions of interest and the results from linkage 25,72 and association studies [38][39][40]42,73,74 (see Figure 1, Tables 1 and 2). Of special interest are the regions 7q21-q22 and 7q31-q32.…”
mentioning
confidence: 99%
“…Genomewide linkage scans, an unbiased approach to localize genetic factors, have identified several chromosomal regions as promising locations for autism vulnerability genes, including peaks on chromosomes 2q, 7q, 15q, and 17q (5)(6)(7)(8). This genetic approach to identify susceptibility genes is very powerful, but the heterogeneity present within autism families has led thus far to mixed success in identifying candidate genes (9,10).…”
mentioning
confidence: 99%